Cause analysis and nursing management of peritoneal dialysis -associated refractory peritonitis (腹膜透析相关性难治性腹膜炎原因分析及护理体会) - RAN Lei (冉蕾); LI Huiyan (李会彦); LI Hanshuang (李韩爽); FAN Jiaojiao (范娇娇) (中西医结合护理)
To analyze the potential causes of peritoneal dialysis-associated refractory peritonitis and summarize related nursing measures. The clinical treatment and nursing process of two cases of peritoneal dialysis-associated refractory peritonitis were retrospectively analyzed. The operating procedure of peritoneal dialysis was not strictly followed in these two patients with slim body type and hypoproteinemia, and treatment was delayed due to insufficient awareness about peritoneal dialysis -associated peritonitis. Anti-infective treatment was administrated for intra-abdominal and peripheral infection, and treatment was switched to hemodialysis as no obvious improvement of bacteriological examination results. The treatment environment, operation procedure, intestinal factor and awareness of disease were main factors influencing the peritoneal dialysis -associated refractory peritonitis, and efforts should be made to enhance the self-management skills of peritoneal dialysis patients. (探讨腹膜透析相关性难治性腹膜炎潜在原因及拔管后相应的护理措施。回顾性分析科室2例难治性腹膜炎患者的临床诊疗及护理经过, 总结疾病临床特征及护理经验。2例患者均体型偏瘦, 且存在低蛋白血症, 日常未严格按操作规程进行, 同时未引起对腹膜透析相关性腹膜炎的重视度, 导致延时就诊。入院后给予腹腔及外周抗感染治疗后10～20 d, 腹腔细菌学检查无明显改善, 给予拔管, 改行血液透析。环境、操作、肠道原因、营养状态、对腹膜炎的认识及重视度是导致难治性腹膜炎发生的原因, 应加强对腹膜透析患者的自我管理。)